2003
DOI: 10.1021/ef030010w
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of HCl and SO2 on NOx Formation in Coal Flames

Abstract: The effect of HCl and SO2 on NO x formation in coal flames was investigated experimentally and kinetically in an entrained flow combustion reactor (EFCR). Two bituminous coals (German “Goettelborn” and a Polish coal) were used as fuels with a feeding rate of 1 or 1.5 kg/h. HCl or SO2 is added into the primary air for injection into the reactor. Experimental results indicate that when HCl is added in the range from 0 to 610 ppmv, NO x emissions are reduced by 0−20%. The measured NO x profiles along the react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…In order to consider the effect of HCl or SO 2 released from the coals on CO emissions, the baselines of HCl and SO 2 concentrations were measured for some operating conditions [24]. For various operating conditions, the base emission of HCl at the reactor exit varied in the range of 29 -83 ppmv for Polish coal, and 30 -95 ppmv for Goettelborn coal.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to consider the effect of HCl or SO 2 released from the coals on CO emissions, the baselines of HCl and SO 2 concentrations were measured for some operating conditions [24]. For various operating conditions, the base emission of HCl at the reactor exit varied in the range of 29 -83 ppmv for Polish coal, and 30 -95 ppmv for Goettelborn coal.…”
Section: Resultsmentioning
confidence: 99%
“…The trials were conducted in an entrained flow combustion reactor (EFCR) and the detailed description of this reactor may be found in the other paper [24]. The electrically heated reactor has five regulated heating zones with a maximum temperature of 1673 K. The combustion air can be preheated up to approximately 673 K. The carrying air with pulverised coal enters the burner centre, surrounded by the primary air and the secondary air.…”
Section: Experimental Facilitymentioning
confidence: 99%
See 1 more Smart Citation
“…During combustion or gasification, the chlorine is released as HCl and Cl 2 , which are known to act as inhibitor by catalyzing the recombination of radicals O, H, OH, and HO 2 in the flame. Therefore, HCl is likely to affect the oxidation of CO [2][3][4][5] and the formation of NO [6,7] in combustion.…”
Section: Introductionmentioning
confidence: 99%
“…Wei et al [7] found that the HCl addition decreased NO emission in pulverized coal flames and explained it by the competition between the reactions of NO formation and reduction. In the present paper, in order to study the effect of HCl on NO formation in gaseous volatile combustion, the experiments are conducted in an entrained flow reactor (EFR), for the first time.…”
Section: Introductionmentioning
confidence: 99%